Pemberdayaan Pelaku UMKM Perikanan Melalui Digitalisasi di Kabupaten Maluku Tengah dengan Metode ABCD - Fauziyah, Nida Nurlivi; Jawahir, Moh. (Universitas Batanghari Jambi, 2024)
Central Maluku Regency MSMEs are dominated by players in the fisheries sector, due to the abundant potential for marine products in the area. But unfortunately the abundance of marine products is not directly proportional to the income of the people there. The main objective of this research activity is to increase MSMEs' understanding of the importance of digitalization in the 4.0 revolution era and to improve MSMEs' abilities and skills regarding business management from upstream to downstream using the latest technology and information in order to increase income. The method for implementing this research activity uses the ABCD (Asset Base Community Development) approach which prioritizes the use of assets and potential that exist around the community for sustainable economic growth to form community independence in increasing income so that their welfare will also increase. Coupled with a SWOT analysis to identify internal and external factors in the state of Central Maluku Regency MSMEs. The results of this research are that MSEs need to be given training in Market Research, Branding, Digital Literacy and Financial Literacy.